Hexagonal boron nitride / titanium dioxide heterojunction-based doped material and preparation method thereof
By doping N, Fe, and F elements into the hexagonal boron nitride/titanium dioxide heterojunction, high-efficiency photocatalytic materials are prepared, which solves the problem of low light absorption efficiency of existing photocatalytic materials, and achieves the effect of efficient use of sunlight and reducing costs.
Patent Information
- Application Number
- CN202510209755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
AI Technical Summary
The existing photocatalytic materials have low light absorption efficiency in the ultraviolet light range, high energy consumption, expensive manufacturing, and difficult to effectively utilize sunlight.
A hexagonal boron nitride/titanium dioxide heterojunction doping material is used to dopate N elements, Fe elements, and F elements in the heterojunction, combined with chemical vapor deposition, atomic layer deposition and ion implantation methods to prepare materials with high light absorption efficiency.
It significantly improves the light absorption efficiency of the material within the ultraviolet light range, enhances the photocatalytic activity, improves the utilization rate of sunlight, and reduces the manufacturing and maintenance costs of the material.
Smart Images

Figure CN119897144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a hexagonal boron nitride / titanium dioxide heterojunction doping material and a preparation method thereof. Background Art
[0002] While the era of rapid industrialization has provided convenience to people's lives, the excessive consumption of fossil energy has caused energy crises and environmental pollution. Among them, water pollution is one of the main problems of environmental pollution. The ideal way to solve the water pollution problem is to use semiconductor photocatalysis technology. Semiconductor photocatalysis technology is a green and efficient governance method, but it faces key problems of high energy consumption and expensive manufacturing in actual application scenarios. Therefore, how to improve light absorption efficiency is one of the important research directions at present.
[0003] Titanium dioxide ( ) is a common photocatalytic material. Its unique photocatalytic performance is not only affected by its inherent physical and chemical properties, but also by the ) particle morphology and structural properties, but its broadband limits its efficiency in utilizing visible light. Titanium dioxide ( ) only responds to ultraviolet light, and ultraviolet light only accounts for 5% of sunlight. Therefore, how to improve the light absorption capacity and carrier migration rate of the material is an important issue currently faced in improving photocatalytic performance. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides a hexagonal boron nitride / titanium dioxide heterojunction doping material, which can improve the light absorption efficiency of the material in the ultraviolet light range.
[0005] The second object of the present invention is to provide a method for preparing a hexagonal boron nitride / titanium dioxide heterojunction doping material.
[0006] The technical solution of the present invention to solve the above technical problems is:
[0007] A hexagonal boron nitride / titanium dioxide heterojunction doping material, composed of h-BN and A heterojunction is formed; and N element, Fe element and F element are doped in the heterojunction, wherein the concentrations of the doped N element, Fe element and F element are 0.1-3at%, 0.05-2at% and 0.1-3at% respectively.
[0008] Preferably, the h-BN and the The mass ratio is 1:1 to 1:5.
[0009] A method for preparing a hexagonal boron nitride / titanium dioxide heterojunction doping material comprises the following steps:
[0010] Step S1: growing several layers of h-BN thin films on a silicon-based substrate using a chemical vapor deposition method;
[0011] Step S2: Depositing on the surface of h-BN film by atomic layer deposition film;
[0012] Step S3: Use ion implantation or heat treatment to introduce N, Fe and F into the In the heterojunction, the concentrations of doped N, Fe, and F are 0.1-3at, 0.05-2at, and 0.1-3at, respectively;
[0013] Step S4: Annealing at 300° C.-600° C. in an inert atmosphere for 1-3 hours until the doping elements are evenly distributed and crystal defects are repaired.
[0014] Preferably, in step S1, the chemical vapor deposition method comprises the following steps:
[0015] Step S11: cutting the copper foil into a size of 2 cm×2 cm, and ultrasonically cleaning it with acetone, ethanol and deionized water for 10 minutes in sequence to remove surface contaminants;
[0016] Step S12: Place the cleaned copper foil into a CVD reactor and evacuate to Pa, then hydrogen was introduced as a carrier gas with a flow rate of 50 sccm, heated to 1000°C and maintained for 30 minutes to clean and activate the copper foil surface;
[0017] Step S13: introducing a precursor gas composed of a boron source and a nitrogen source to grow an h-BN film for 1 hour;
[0018] Step S14: After the growth is completed, the precursor gas is turned off and cooled to room temperature in a hydrogen atmosphere;
[0019] Step S15: Using wet transfer technology to transfer the h-BN film to On substrate.
[0020] Preferably, in step S1, the thickness of the prepared h-BN film is 1 nm-10 nm.
[0021] Preferably, in step S2, the steps of the atomic layer deposition method are:
[0022] Step S21: placing the sample prepared in step S15 into an ALD reaction chamber and heating it to 150° C.-300° C.;
[0023] Step S22: Deposition is performed using a titanium source and an oxygen source, and the cycle is repeated for 200 times to obtain a layer with a thickness of 10 nm to 50 nm. Film, wherein each cycle comprises the following steps:
[0024] A titanium source is introduced to make it adsorb on the surface of the h-BN film;
[0025] Purging with inert gas to remove unreacted titanium source;
[0026] An oxygen source is introduced to react with the adsorbed titanium source to generate ;
[0027] The inert gas purge is used again to remove by-products and unreacted oxygen source.
[0028] Preferably, in step S2, the The thickness of the film is 20 nm.
[0029] Preferably, in step S3, the steps of the ion implantation method are:
[0030] Step S31: The sample was placed in an ion implantation device and injected with nitrogen source, iron source and fluorine source respectively. The injection energy of nitrogen source was 30 keV and the injection dose was ions / cm²; the implantation energy of the iron source is 50keV and the implantation dose is ions / cm²; the injection energy of the fluorine source is 20keV, and the injection dose is ions / cm²;
[0031] Step S32: After the injection is completed, take out the sample.
[0032] Preferably, in step S4, the annealing process is:
[0033] Step S41: placing the doped sample into a tube furnace, and introducing an inert gas or a reducing gas as a protective gas;
[0034] Step S42: heating to 500°C at a rate of 5°C / min and maintaining for 2h;
[0035] Step S43: After annealing is completed, the temperature is lowered to room temperature at a rate of 5°C / min.
[0036] An application of a hexagonal boron nitride / titanium dioxide heterojunction doping material in a photocatalytic reaction, wherein the photocatalytic reaction includes water decomposition to produce hydrogen, pollutant degradation and titanium dioxide reduction.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] 1. In the present invention, h-BN has high chemical stability, thermal stability, wide band gap, biocompatibility and environmental friendliness, which can effectively make up for the shortcomings of traditional photocatalytic materials. By constructing a heterojunction, the energy band can be regulated, the light absorption range can be widened, and the light absorption capacity can be enhanced; secondly, due to the built-in electric field formed by the difference in the energy band structure, the photogenerated electrons will The conduction band of h-BN migrates to the conduction band of h-BN, and the photogenerated holes migrate from the valence band of h-BN to valence band, which can improve the separation efficiency of photogenerated carriers, thereby significantly improving the light absorption efficiency and catalytic activity of photocatalytic materials.
[0039] 2. The present invention constructs a layered Heterojunction composite materials can improve the light absorption efficiency of materials in the ultraviolet range by Doping N, Fe, and F elements in the photocatalyst can increase the migration rate of electrons and holes, thereby promoting redox reactions, which provides a reference for further improving the application effect of photocatalysts in sewage treatment.
[0040] 3. The present invention Doping N, Fe and F elements in the material has its specific effects, which can improve the electronic structure, light absorption capacity and catalytic activity of the material from different aspects, specifically:
[0041] (1) Doping with N elements has the following advantages:
[0042] First, it can improve the photocatalytic efficiency: N ion doping Introducing defect energy levels into the forbidden band, narrowing the band gap, and promoting the energy reduction of photogenerated carriers transitioning to the corresponding energy band; secondly, it can improve light absorption: The band gap is wide (3.84eV) and can only absorb ultraviolet light (accounting for about 5% of sunlight). After doping with N elements, the material can absorb visible light (accounting for about 43% of sunlight), thereby significantly improving the utilization rate of sunlight; finally, the conductivity of the material is improved: N elements, as N-type dopants, can increase the concentration of free electrons (photogenerated carriers), thereby improving the conductivity of the material and promoting photocatalytic reactions.
[0043] (2) Doping with Fe element has the following advantages:
[0044] First, improve the photocatalytic efficiency: Fe ions ( / ) doping will introduce intermediate energy levels in the band gap, promote the transition of photogenerated carriers, reduce the recombination of carriers, and thus improve the efficiency of photocatalysis; secondly, it can enhance magnetism: Fe ion doping may give the material magnetism, which is convenient for the recovery and reuse of the catalyst; finally, it can improve the catalytic activity. Fe ions can act as active sites, participate in the photocatalytic reaction, and accelerate the progress of the photocatalytic reaction.
[0045] (3) Doping with F element has the following advantages:
[0046] First, it can improve the photocatalytic efficiency: F ions have high electronegativity and can form strong bonds with Ti atoms and B atoms on the surface of the material, and can fill O vacancies or other defects on the surface of the material. Doping with F ions can modify the surface of the material and reduce surface defects, thereby inhibiting carrier recombination and extending the carrier life. Secondly, it can improve the durability of the material: F ions can form strong bonds with the surface of the material, inhibit the photocorrosion of the material in the photocatalytic reaction, enhance the chemical stability of the surface, and enable the material to maintain high efficiency in a long-term photocatalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a schematic diagram of the structure of the hexagonal boron nitride / titanium dioxide heterojunction doping material of the present invention.
[0048] Figure 2 After doping with Fe Schematic diagram of the heterojunction structure.
[0049] Figure 3 After doping with N element Schematic diagram of the heterojunction structure.
[0050] Figure 4 After doping with F element Schematic diagram of the heterojunction structure.
[0051] Figure 5 The embodiment of the present invention provides , without any doping Heterojunction, and after doping with N, Fe, and F elements Optical absorption spectrum of heterojunction.
[0052] Figure 6 Based on the Hall effect test, the , without any doping Heterojunction, and after doping with N, Fe, and F elements Graph of carrier mobility of a heterojunction.
[0053] Figure 7 The embodiment of the present invention provides , without any doping Heterojunction, and after doping with N, Fe, and F elements Comparison of photocatalytic activity of heterojunction under ultraviolet light, where the horizontal axis is the degradation time (Time), in min; the vertical axis is the degradation rate of the sample to methyl orange / ,in, is the concentration after degradation, is the concentration of degradation solution before illumination.
[0054] Figure 8 This is the energy band arrangement diagram before and after the heterojunction is formed. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0056] See also Figure 1-Figure 8 The present invention is based on hexagonal boron nitride (h-BN) / titanium dioxide ( ) Heterojunction doping material, consisting of h-BN and A heterojunction is formed; and N element, Fe element and F element are doped in the heterojunction, wherein the concentrations of the doped N element, Fe element and F element are 0.1-3at%, 0.05-2at% and 0.1-3at% respectively.
[0057] In the present invention, considering that the ability of photocatalysis for sewage treatment is mainly related to the light absorption performance and catalytic activity of the photocatalytic material itself, starting from material design and modification, the construction of heterojunction is first considered. Since h-BN has high chemical stability, thermal stability, wide band gap, biocompatibility and environmental friendliness, it can effectively make up for the shortcomings of traditional photocatalytic materials. By constructing a heterojunction, the energy band can be regulated, the light absorption range can be widened, and the light absorption capacity can be enhanced; secondly, due to the built-in electric field formed by the difference in the energy band structure, the photogenerated electrons will The conduction band of h-BN migrates to the conduction band of h-BN, and the photogenerated holes migrate from the valence band of h-BN to valence band, which can improve the separation efficiency of photogenerated carriers, thereby significantly improving the light absorption efficiency and catalytic activity of photocatalytic materials.
[0058] In addition, in the present invention Doping N, Fe and F elements in the material has its specific role, which can improve the electronic structure, light absorption capacity and catalytic activity of the material from different aspects, specifically:
[0059] (1) Doping with N element has the following advantages:
[0060] First, it can improve the photocatalytic efficiency: N ion doping Introducing defect energy levels into the forbidden band, narrowing the band gap, and promoting the energy reduction of photogenerated carriers transitioning to the corresponding energy band; secondly, it can improve light absorption: The band gap is wide (3.84eV) and can only absorb ultraviolet light (accounting for about 5% of sunlight). After doping with N elements, the material can absorb visible light (accounting for about 43% of sunlight), thereby significantly improving the utilization rate of sunlight; finally, the conductivity of the material is improved: N elements, as N-type dopants, can increase the concentration of free electrons (photogenerated carriers), thereby improving the conductivity of the material and promoting photocatalytic reactions.
[0061] (2) Doping with Fe element has the following advantages:
[0062] First, improve the photocatalytic efficiency: Fe ions ( / ) doping will introduce intermediate energy levels in the band gap, promote the transition of photogenerated carriers, reduce the recombination of carriers, and thus improve the efficiency of photocatalysis; secondly, it can enhance magnetism: Fe ion doping may give the material magnetism, which is convenient for the recovery and reuse of the catalyst; finally, it can improve the catalytic activity. Fe ions can act as active sites, participate in the photocatalytic reaction, and accelerate the progress of the photocatalytic reaction.
[0063] (3) Doping with F element has the following advantages:
[0064] First, it can improve the photocatalytic efficiency: F ions have high electronegativity and can form strong bonds with Ti atoms and B atoms on the surface of the material, and can fill O vacancies or other defects on the surface of the material. Doping with F ions can modify the surface of the material and reduce surface defects, thereby inhibiting carrier recombination and extending the carrier life. Secondly, it can improve the durability of the material: F ions can form strong bonds with the surface of the material, inhibit the photocorrosion of the material in the photocatalytic reaction, enhance the chemical stability of the surface, and enable the material to maintain high efficiency in a long-term photocatalytic reaction.
[0065] See also Figure 1-Figure 8 , the h-BN and the The mass ratio is 1:1 to 1:5.
[0066] See also Figure 1-Figure 8 The method for preparing a hexagonal boron nitride / titanium dioxide heterojunction doping material of the present invention comprises the following steps:
[0067] Step S1: growing a single layer or a multilayer h-BN film on a silicon-based substrate by a chemical vapor deposition method;
[0068] Step S2: Depositing on the surface of h-BN film by atomic layer deposition film;
[0069] Step S3: Use ion implantation or heat treatment to introduce N, Fe and F into the In the heterojunction, the concentrations of doped N, Fe, and F are 0.1-3at%, 0.05-2at%, and 0.1-3at, respectively; specifically:
[0070] exist The heterojunction is doped with N elements to obtain Samples, in The heterojunction is doped with Fe to obtain Samples, in The heterojunction is doped with F element to obtain sample;
[0071] Step S4: Annealing at 300° C.-600° C. in an inert atmosphere for 1 h-3 h until the doping elements are evenly distributed and crystal defects are repaired.
[0072] See also Figure 1-Figure 8 In step S1, the chemical vapor deposition method comprises:
[0073] Step S11: copper foil is selected as the growth substrate because its surface is flat and easy to grow h-BN. Therefore, the copper foil is cut into 2 cm×2 cm size and ultrasonically cleaned with acetone, ethanol and deionized water for 10 minutes in sequence to remove surface oxides and impurities;
[0074] Step S12: Place the cleaned copper foil into a CVD reactor and evacuate to Pa, then hydrogen is introduced as a carrier gas at a flow rate of 50 sccm, and heated to 900°C-1000°C (1000°C is selected in this embodiment) and maintained for 30 minutes to clean and activate the copper foil surface;
[0075] Step S13: introducing a precursor gas, wherein the precursor gas is selected from a boron source (such as borane) or Boron Trichloride In this embodiment, borane is selected , flow rate is 5sccm) and nitrogen source (such as ammonia , flow rate of 50sccm) as the reaction gas, and introduce hydrogen ( ) as carrier gas and reducing agent, control the precursor gas and flow ratio ( : : =1:10:100), wait for 30 minutes to 2 hours; grow h-BN film for 1 hour;
[0076] Step S14: After the growth is completed, the precursor gas is turned off. Cool to room temperature in atmosphere;
[0077] Step S15: Using wet transfer technology to transfer the h-BN film to On the substrate; in this embodiment, using The substrate serves as a target base.
[0078] See also Figure 1-Figure 8 In step S1, the thickness of the h-BN film is 1nm-10nm.
[0079] See also Figure 1-Figure 8 In step S2, the steps of the atomic layer deposition method are:
[0080] Step S21: placing the sample obtained in step S15 into an ALD reaction chamber and heating it to 150° C.-300° C. (preferably 200° C. in this embodiment);
[0081] Step S22: Using a titanium source (such as titanium tetrachloride ) and an oxygen source (such as water or ozone ) for deposition, and repeat 200 cycles until the desired thickness of 10nm-50nm is achieved. Film, wherein each cycle comprises the following steps:
[0082] Titanium tetrachloride was introduced with a pulse time of 0.1 second to make it adsorb on the surface of the h-BN film;
[0083] Purge with an inert gas (such as nitrogen, helium or argon) for 10 seconds to remove unreacted titanium tetrachloride;
[0084] Add an oxygen source (such as water) or ozone ), with a pulse time of 0.1 second, to react with the adsorbed titanium tetrachloride to generate ;
[0085] Purge again with an inert gas (such as nitrogen, helium or argon) for 10 seconds to remove by-products and unreacted oxygen source;
[0086] Step S23: After the deposition is completed, annealing is performed in an inert gas (300°C-500°C) to improve film crystallinity.
[0087] In this example, the prepared The thickness of the film is 20 nm.
[0088] See also Figure 1-Figure 8 In step S3, the steps of the ion implantation method are:
[0089] Step S31: The samples were placed in the ion implantation equipment and injected (e.g. using nitrogen or ammonia as the nitrogen source), / and (For example, hydrogen fluoride or fluorine gas is used as the fluorine source), wherein, The implantation energy is 30keV and the implantation dose is ions / cm²; The implantation energy is 50keV and the implantation dose is ions / cm²; The implantation energy is 20keV and the implantation dose is ions / cm²;
[0090] Step S32: After the injection is completed, take out the sample.
[0091] See also Figure 1-Figure 8 In step S4, the annealing process is:
[0092] Step S41: Select annealing equipment, use a tube furnace or rapid thermal annealing (RTA) equipment; in this embodiment, a tube furnace is used; put the doped sample into the tube furnace, and use an inert gas (such as nitrogen or argon) or a reducing gas (such as hydrogen) as a protective gas with a flow rate of 100 sccm; anneal for 1-3 hours to repair the crystal damage caused by ion implantation and make the doping elements evenly distributed and enter the lattice position;
[0093] Step S42: heating to 500°C at a rate of 5°C / min and maintaining for 2h;
[0094] Step S43: After annealing is completed, the temperature is lowered to room temperature at a rate of 5°C / min.
[0095] See also Figure 1-Figure 8 , the present invention is based on hexagonal boron nitride (h-BN) / titanium dioxide ( ) Heterojunction doped materials for performance testing:
[0096] (1) Light absorption performance test
[0097] Place the sample in the test chamber, measure its light absorption spectrum in the wavelength range of 200nm-800nm, compare the light absorption spectrum before and after doping, and analyze the changes in the light absorption range.
[0098] like Figure 5 As shown in Figure 2, the light absorption of the samples before and after doping in the visible light region (400nm-700nm) is significantly enhanced, indicating that the hexagonal boron nitride (h-BN) / titanium dioxide ( ) The heterojunction successfully broadened the light absorption range after being doped with N, Fe and F elements respectively; the red shift and blue shift phenomena of the light absorption spectrum overlapped, further improving the photocatalytic absorption efficiency.
[0099] (2) Carrier mobility test
[0100] Four electrodes are prepared on the sample surface to form a Van der Pauw structure; a constant current is applied, and the Hall voltage and resistivity are measured; and the carrier concentration and mobility are calculated.
[0101] like Figure 6 As shown in the figure, the carrier mobility of the samples doped with N, Fe and F elements is significantly improved. Doping with N introduces defect energy levels and narrows the band gap. Doping with Fe can increase the free electron concentration of the material. Doping with F can reduce surface defects and optimize the carrier transmission path.
[0102] Hall effect test results show that temperature has a significant effect on carrier mobility, which usually reaches a peak at around 300K and then decreases slightly at high temperatures. At room temperature, the carrier mobility increases from 10cm² / Vs before doping to 50cm² / / Vs after doping.
[0103] (3) Photocatalytic performance
[0104] The sample was placed in a reactor containing a methyl orange solution (10 mg / L); a 300 W xenon lamp was used to simulate sunlight irradiation, and samples were taken every 10 minutes; a UV-visible spectrophotometer was used to measure the absorbance of the methyl orange solution and calculate the degradation rate.
[0105] like Figure 7 As shown in the figure, the degradation rate of methyl orange by the samples doped with N, Fe and F elements reached 95% within 60 minutes, while the degradation rate of the samples not doped with N, Fe and F elements was only 53.6%; therefore, doping with N, Fe and F elements can significantly improve the photocatalytic efficiency, which indicates that the improvement of carrier mobility directly promotes the progress of photocatalytic reaction.
[0106] Figure 8 This is the energy band arrangement diagram before and after the heterojunction is formed. After the formation, a large amount of negative charges are The negative charges accumulate on the surface of h-BN, and due to the transfer of these negative charges, the positive charges are retained on the h-BN surface, thus forming a built-in electric field. Under the action of the built-in electric field, the photogenerated electrons and holes migrate in opposite directions, respectively, which effectively inhibits the recombination of holes and carriers, prolongs the carrier lifetime, and thus enhances the efficiency of the photocatalytic reaction.
[0107] Finally, the present invention proposes Heterojunction doped materials have the following advantages:
[0108] The present invention proposes Heterojunction doped materials broaden the visible light absorption range and significantly improve the utilization rate of sunlight;
[0109] The present invention proposes Heterojunction doping materials reduce carrier recombination and extend carrier lifetime, thereby improving catalytic efficiency;
[0110] The present invention proposes Heterojunction doped materials have high chemical and thermal stability, which significantly improves the durability of the materials and reduces replacement and maintenance costs;
[0111] The present invention proposes Heterojunction doped materials have certain magnetic properties and can be recovered and reused by applying an external magnetic field;
[0112] The present invention proposes Heterojunction doped materials are non-toxic and non-polluting, meeting environmental protection requirements.
[0113] The above is a preferred embodiment of the present invention, but the embodiment of the present invention is not limited to the above content. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A hexagonal boron nitride / titanium dioxide heterojunction doping material, characterized in that: h-BN and A heterojunction is formed; and N element, Fe element and F element are doped in the heterojunction, wherein the concentrations of the doped N element, Fe element and F element are 0.1-3at%, 0.05-2at% and 0.1-3at% respectively.
2. The hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 1, characterized in that: The h-BN and the The mass ratio is 1:1 to 1:
5.
3. A method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 1 or 2, characterized in that: The following steps are involved: Step S1: growing several layers of h-BN thin films on a silicon-based substrate using a chemical vapor deposition method; Step S2: Depositing on the surface of h-BN film by atomic layer deposition film; Step S3: Use ion implantation or heat treatment to introduce N, Fe and F into the In the heterojunction, the concentrations of doped N, Fe, and F are 0.1-3at, 0.05-2at, and 0.1-3at, respectively; Step S4: Annealing at 300° C.-600° C. in an inert atmosphere for 1-3 hours until the doping elements are evenly distributed and crystal defects are repaired.
4. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 3, characterized in that: In step S1, the chemical vapor deposition method comprises the following steps: Step S11: cutting the copper foil into a size of 2 cm×2 cm, and ultrasonically cleaning it with acetone, ethanol and deionized water for 10 minutes in sequence to remove surface contaminants; Step S12: Place the cleaned copper foil into a CVD reactor and evacuate to Pa, then hydrogen was introduced as a carrier gas with a flow rate of 50 sccm, heated to 1000°C and maintained for 30 minutes to clean and activate the copper foil surface; Step S13: introducing a precursor gas composed of a boron source and a nitrogen source to grow an h-BN film for 1 hour; Step S14: After the growth is completed, the precursor gas is turned off and cooled to room temperature in a hydrogen atmosphere; Step S15: Using wet transfer technology to transfer the h-BN film to On substrate.
5. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 4, characterized in that: In step S1, the thickness of the prepared h-BN film is 1 nm-10 nm.
6. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 4, characterized in that: In step S2, the steps of the atomic layer deposition method are: Step S21: placing the sample prepared in step S15 into an ALD reaction chamber and heating it to 150° C.-300° C.; Step S22: Deposition is performed using a titanium source and an oxygen source, and the cycle is repeated for 200 times to obtain a layer with a thickness of 10 nm to 50 nm. Film, wherein each cycle comprises the following steps: A titanium source is introduced to make it adsorb on the surface of the h-BN film; Purging with inert gas to remove unreacted titanium source; An oxygen source is introduced to react with the adsorbed titanium source to generate ; The inert gas purge is used again to remove by-products and unreacted oxygen source.
7. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 6, characterized in that: In step S2, the The thickness of the film is 20 nm.
8. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 6, characterized in that: In step S3, the steps of the ion implantation method are: Step S31: The sample was placed in an ion implantation device and injected with nitrogen source, iron source and fluorine source respectively. The injection energy of nitrogen source was 30 keV and the injection dose was ions / cm²; the implantation energy of the iron source is 50keV and the implantation dose is ions / cm²; the injection energy of the fluorine source is 20keV, and the injection dose is ions / cm²; Step S32: After the injection is completed, take out the sample.
9. The method for preparing the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 8, characterized in that: In step S4, the annealing process is: Step S41: placing the doped sample into a tube furnace, and introducing an inert gas or a reducing gas as a protective gas; Step S42: heating to 500°C at a rate of 5°C / min and maintaining for 2h; Step S43: After annealing is completed, the temperature is lowered to room temperature at a rate of 5°C / min.
10. An application of the hexagonal boron nitride / titanium dioxide heterojunction doping material according to claim 1 in a photocatalytic reaction, characterized in that: The photocatalytic reactions include water decomposition to produce hydrogen, pollutant degradation and titanium dioxide reduction.
Citation Information
Patent Citations
Iron, nitrogen and fluoride co-doped titanium dioxide (TiO2) photocatalyst and application thereof in degrading organic pollutants in visible light
CN102500406A
Preparation method of h-BN / TiO2 composite material with high photocatalytic performance
CN109107598A
Boron nitride composite thin film used for metal surface corrosion protecting, making method of thin film, and application
CN110453195A
Method for fixed-point doping of single atom or few atoms
CN118800648A
Defect engineering in metal oxides via surfaces
US20120172648A1
Cited By
Flexible substrate material doped with two-dimensional material and preparation method of sensor of flexible substrate material
CN120793914A
A flexible substrate material doped with a two-dimensional material and a method for manufacturing a sensor thereof
CN120793914B
S-type heterojunction composite photocatalyst of flower-shaped BN / TiO2 as well as preparation method and application of S-type heterojunction composite photocatalyst
CN120900685A